Associations Between Movement Behaviors and Emotional Changes in Toddlers and Preschoolers During Early Stages of the COVID-19 Pandemic in Chile - Aguilar-Farias, Nicolas; Toledo-Vargas, Marcelo; Miranda-Marquez, Sebastian; Cortinez-O'Ryan, Andrea; Martino-Fuentealba, Pia; Cristi-Montero, Carlos; Rodriguez-Rodriguez, Fernando; Guarda-Saavedra, Paula; Del Pozo Cruz, Borja; Okely, Anthony D. (Frontiers in Pediatrics, 2021)
Background: There is limited evidence about emotional and behavioral responses in toddlers and preschoolers during the novel coronavirus (COVID-19) pandemic, particularly in Latin America. Objective: To assess associations between changes in movement behaviors (physical activity, screen time and sleeping) and emotional changes in toddlers and preschoolers during early stages of the pandemic in Chile. Methods: A cross-sectional study conducted from March 30th to April 27th, 2020. Main caregivers of 1- to 5-year-old children living in Chile answered an online survey that included questions about sociodemographic characteristics, changes in the child’s emotions and behaviors, movement behaviors and caregivers’ stress during the pandemic. Multiple linear regressions were used to assess the association between different factors and emotional changes in toddlers and preschoolers. Results: In total, 1727 caregivers provided complete data on emotional changes for children aged 2.9±1.36 years old, 47.9% girls. A large proportion of toddlers and preschoolers in Chile experienced emotional and behavioral changes. Most caregivers reported that children were ‘more affectionate’ (78.9%), ‘more restless’ (65.1%), and ‘more frustrated’ (54.1%) compared with pre-pandemic times. Apart from changes in movement behaviors, factors such as child age, caregivers’ age and stress, and residential area (urban/rural) were consistently associated with changes in emotions and behaviors. Conclusion: The pandemic substantially affected the emotions and behaviors of toddlers and preschoolers in Chile. Mental health promotion programs should consider multilevel approaches in which the promotion of movement behaviors and support for caregivers should be essential pieces for future responses.